Modern distribution system expansion planning considering new market designs: Review and future directions - de Lima, Tayenne Dias; Lezama, Fernando; Soares, João; Franco, John F. [UNESP]; Vale, Zita (Elsevier, 2024)
The distribution system is undergoing profound transformations with decarbonization efforts through the rapid integration of renewable energy and the consequent transition of the distribution network from passive to active. Nonetheless, environmental and economic urgency requires redesigning the existing distribution system. New operational standards and technologies such as electric vehicles, demand response, energy storage systems, energy hubs, microgrids, and transactive energy markets have been developed. Distribution system expansion planning plays a crucial role in supporting this transition process. This work presents a review of planning proposals published in the last decade considering flexibility, local markets, and microgrid concepts. The main aspects of these works are described in terms of solution methods, expansion alternatives, planning periods, uncertainties, and contributions, among others. Furthermore, planning proposals are analyzed and classified taking into account new market designs. In addition, future trends are identified. Finally, this review can be used as a tool and guide for different stakeholders on current practices and new trends regarding the distribution system expansion planning, serving as a foundation for future investigations.
Keywords: Distribution system planning; energy markets; flexible resources; local market; non-network solutions; smart grid